Diffusion of Technology during Covid Period - Sudheesh B (East Asian Journal of Multidisciplinary Research, 2022)
During the Covid period the people are depending broadband internet connectivity for their work. Faster and reliable connectivity is becoming an essential criterion in our daily life. The pandemic period has provided an opportunity for fast diffusion of technology. So uninterrupted and high speed data services has become essential. During the lock-down period people prefer online platforms of food distribution services for ordering food .The covid crisis has changed everything to online. People are forced to adapt to new technologies during the covid period. This article narrate consumer preference towards various broadband internet services and the diffusion of broad band internet services.